Homers at the Interface between Reward and Pain - Obara, Ilona; Goulding, Scott; Gould, Adam; Lominac, Kevin; Hu, Jia-Hua; Zhang, Ping Wu; von Jonquieres, Georg; Dehoff, Marlin; Xiao, Bo; Seeburg, Peter H.; Worley, Paul; Klugmann, Matthias; et al. (Frontiers in Psychiatry, 2013)
Pain alters opioid reinforcement, via neuroadaptations within ascending pain pathways interacting with the limbic system. Nerve injury increases expression of glutamate receptors and Homer scaffolding proteins throughout the pain processing pathway and these molecules regulate behavioral sensitivity to various addictive drugs. Thus, we investigated a role for Homers in the interactions between pain and drug reward in mice. Chronic constriction injury of the sciatic nerve (CCI) elevated Homer1b/c and/or Homer2a/b within all mesolimbic structures examined and the Homer increases coincided with elevated mGluR5, GluN2A/B, and the activational state of down-stream kinases. Behaviorally, CCI mice showed pain hypersensitivity and a conditioned place-aversion (CPA) at a low heroin dose that supported conditioned place-preference (CPP) in naïve controls. Null mutations of Homer1a, Homer1 and Homer2, as well as transgenic disruption of mGluR5-Homer interactions, either attenuated or completely blocked low-dose heroin CPP, and none of the CCI mutant strains exhibited heroin-induced CPA. However, heroin CPP did not depend upon full Homer1c expression within the nucleus accumbens (NAC), as CPP occurred in controls infused locally with shRNA-Homer1c, although intra-NAC and/or intrathecal cDNA-Homer1c, -Homer1a and –Homer2b infusions (to best mimic CCI’s effects) were sufficient to blunt heroin CPP in uninjured mice. However, arguing against a simple role for CCI-induced increases in either spinal or NAC Homer expression for heroin CPA, cDNA infusion of our various cDNA constructs either did not affect (intrathecal) or attenuated (NAC) heroin CPA. These data implicate increases in glutamate receptor/Homer/kinase activity within limbic structures, perhaps outside the NAC, as possibly critical for switching the incentive motivational properties of heroin following nerve injury, which has relevance for opioid psychopharmacology in individuals suffering from neuropathic pain.